Ovarian cyst in pregnancy: a case report - Patyal, Neha; Banyal, Kajal; Verma, Kavita; Saini, Anamika; Chauhan, Kalpna; Kharb, Renu (International Journal Of Community Medicine And Public Health, 2025)
In this case, we report a 27-year-old multigravida with 20 weeks+2 days presenting with right ovarian cyst with previous LSCS. She presented to the antenatal clinic with amenorrhea since from last 5 months. Her ultrasonography report showed that single live intrauterine gestation of 20 weeks 2 days, fetal cardiac activity presented, liquor was adequate, placenta implanted in fundal region, CL was adequate, internal os closed. The impression was right ovary shows a complex cyst with peripheral partial septations and subtle low-level echoes. Her MRI report showed large well defined cystic lesion in the right adnexa with thick internal septations postero-inferiorly as described, likely complex right ovarian cyst. She was diagnosed to have right ovary cyst along with right fallopian tube and laparotomy proceed with right ovarian cystectomy under CSEA and right salphingectomy was carried out.